Pemberdayaan Masyarakat Kampung Batok dalam Mewujudkan Ekonomi Kreatif di Kota Blitar - Dida Rahmadanik (Exchall: Economic Challenge, 2020)
Creative economy and tourist destinations are two interconnected currencies and need to be developed theoretically. This research discusses community empowerment in The City of Blitar, The focus of research on Kampung Batok which is one of the icons of educational villages that can increase the income of the surrounding community. The problem in Kampung Batok is that the maximum promotion and also the government's participation in developing the creative economy is still not maximal. This research uses the method of literature study, namely the study of research objects in the form of literature works in the form of scientific journals, books, articles in the mass media, and statistical data. With Kampung Batok is able to absorb labor and reduce unemployment in Tanjung Sari Village. What still needs attention is that there has been no training from the Blitar city government in providing training in designing, promoting tourist attractions and also handicrafts in a sustainability way. So far, the government only includes representatives of Kampung Batok group to follow the bazaar at certain events. Keywords: Empowerment, Creative Economy, Educational Tourism